Antisense oligonucleotide p45Skp-2 suppresses migratory chemotactic and metastasis of oral malignant Burkitt’s lymphoma cell through down-regulation of MTA-1 and induction of E-cadherin mechanism - Supriatno, Supriatno; Irnawati, Dyah; Medawati, Ana (Padjadjaran Journal of Dentistry, 2020)
Introduction: Burkitt’s lymphoma is a high-grade B-cell neoplasm and one of the most aggressive malignancies of lymphoid origins which found mainly in the paediatric population. The treatment options of this tumour are still limited. However, a new strategy for refractory tumour, phosphorothioate oligonucleotide antisense technique has watched with keen interest. This study was aimed to examine the effect of antisense p45Skp-2 (Skp-2 AS) suppressed migratory chemotactic and metastasis of oral malignant Burkitt’s lymphoma (Raji) cell through down-regulation of MTA-1 and E-cadherin. Methods: True experiment laboratory with post-test control group design was confirmed in this study. The efficiency of Skp-2 AS in the suppression of cell chemotactic migration was examined by Boyden chamber assay. To evaluate the inhibition of cell metastasis was conducted by decreasing MTA-1 expression protein. The expressions of MTA-1, E-cadherin and α-tubulin protein were investigated by Western blot analysis. Results: The results revealed that the number of chemotactic migration of Skp-2 AS treated Raji cell was significantly decreased when compared with that of sense p45Skp-2 (Skp-2 S) and scrambled control (SC) cells (P<0.05) followed by decreased expressions of MTA-1 protein and overexpression of E-cadherin. Interestingly, the expression of α-tubulin protein as an internal control was approximately similar in each transfectant cells. Conclusion: p45Skp-2 have an antitumor activity via suppression of migratory chemotactic activity and metastasis on oral Burkitt’s lymphoma cells through down-regulation of MTA-1 and induction of E-cadherin proteins targeting this molecule could represent a promising new therapeutic approach for this type of cancer.